Classification of rain types for rain attenuation prediction method improvement based on radar information in tropics - Khairolanuar, Muhamad Haziq; Ismail, Ahmad Fadzil; Jusoh, Ahmad Zamani; Sobli, Nuurul Hudaa (Asian Research Publishing Network (ARPN), 2015)

(untitled)
An investigation has been embarked in classifying the rain types. The Terminal Doppler Weather Radar (TDWR) and rain gauge system are currently installed in Bukit Tampoi, Malaysia, and their data are used in this study. Sampled radar data and rain gauge data collected from January to December 2009 were analyzed. The research methodology involves 2 steps. The first step is the identification of precipitation events within the said period. The second step is “separation” process based on the column reflectivity value at desired location. From our analysis, 32 event data are classified as convective and 175 event data are classified as stratiform